Transmission of world food price changes to markets in Sub-Saharan Africa - Minot, Nicholas (International Food Policy Research Institute, 2011)
The global food crisis of 2007-2008 was characterized by a sharp spike in the prices of most commodities, including staple grains. This analysis examines the degree to which changes in world food markets influence the price of staple foods in Sub-Saharan Africa. The analysis is based on more than 60 price series from 11 African countries. After examining price trends over 2007-2008, we use an error correction model to estimate the degree of price transmission.